Medicinal plants used by communities in the District of Carapajó, Cametá-PA, Amazon, Brazil (Research, Society and Development, 2022)
The present study sought to identify the plant species used for medicinal purposes by the communities of the Carapajó district in the municipality of Cametá, Pará State. During the field work, semi-structured interviews were conducted with 23 people. For the qualitative analyses, the indices of concordance of main use (CUP), concordance (CI) and relative frequency (RF) were used. Forty-five ethnospecies of medicinal plants were listed, distributed in 42 genera and 31 families, among which Asteraceae (4 spp.), Apocynaceae (3 spp.), Fabaceae (3 spp.), Lamiaceae (3 spp.), Amaranthaceae (2 spp.), Bignoniaceae (2 spp.), and Poaceae (2 spp.) accounting for 44.1% of the species recorded in the area. On the other hand, 24 families (55.6%) were represented by only one species each. These ethnospecies were mentioned by native inhabitants of the Carapajó district, who use the leaves (76.7%) of these plants mostly for preparing teas (97.6%) for treating some diseases such as diarrhea, fever, headache, stomach problems, anemia, among others. It became evident how strong the popular culture of using medicinal plants still is in the district of Carapajó, as it is in other traditional communities, showing how important and useful this knowledge about these herbs is for its residents. In view of this, the great concern of the district's herbalists regarding the neglect of the new generations about the learning of this knowledge, which would possibly lead to the loss of this knowledge, is evident.